The Psychological Challenges of Identity Reconstruction Following an Acquired Brain Injury - Glintborg, Chalotte; Krogh, Lærke (Narrative Works)

(untitled) (The University of New Brunswick, 2015)
An acquired brain injury (ABI) has a huge impact on a person’s life and identity. However, identity research in connection with ABI is still sparse. The present study investigates how people with ABI reconstruct their identity in the first year post-injury. Forty-three Danish adults were interviewed (semi- structured interviews) twice: while hospitalized and one year post-injury. Discourse analysis, drawing on the concepts of positioning and agency, was applied in order to investigate developmental processes in self-narratives over time. The analysis reveals that one of the key patterns in identity construction in this cohort is that the psychological changes and identity transitions emerge over time.